Measurement data communication within vehicle battery modules by plastic light guide bodies - Philipp Schiepel and Jonas Ernsting and Florian Rittweger and Günter Müller and Karl-Ragmar Riemschneider and Christian Modrzynski (Haus der Technik Essen HDT, 2021)
Traction batteries for electric vehicles are usually structured in modules of 10-36 cells. These modules have been equipped with a monitoring electronic unit that collects measurement data from all cells and a limited number of other sensors. This module electronic unit communicates with a central battery management system. For the latter, conventional fiber optic data communication with glass or plastic fibers and optical connectors is considered too costly in terms of components and assembly. For this reason, our approach was developed that requires less effort. This concept is based on a common light guide body, which can be produced very easily as a flat transparent plastic part of a few millimeters thickness. This light guide body connects the cells under the top cover of the module.
Keywords: electric vehicle battery; battery module; battery monitoring; light guide body